2007
DOI: 10.3171/spi-07/11/566
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocele formation after anterior lumbar interbody fusion at L4–5

Abstract: ✓ In this report, the authors present the case of patient with a lymphocele in the retroperitoneal area following anterior lumbar interbody fusion at L4–5. A lymphocele is a rare complication of spinal operations, especially lower lumbar spinal surgeries. The authors discuss this complicating factor and describe its features and treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Although lymphangiography is the gold standard for diagnosing a lymphocele, there are complications associated with this procedure such as pulmonary embolus, skin infection, skin necrosis, and lymphatic damage due to contrast use. Benefits of doing this procedure to diagnose a lymphocele are uncertain [ 6 , 8 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although lymphangiography is the gold standard for diagnosing a lymphocele, there are complications associated with this procedure such as pulmonary embolus, skin infection, skin necrosis, and lymphatic damage due to contrast use. Benefits of doing this procedure to diagnose a lymphocele are uncertain [ 6 , 8 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pee et al 28 reported an RPL after anterior lumbar interbody fusion at L4-5, which recurred after ultrasound-guided aspiration; it was eventually managed by open drainage through the previous retroperitoneal approach and application of lyophilized fibrin adhesive around the iliac vessels and prevertebral soft tissues. Wagner et al, 29 in their series of 19 patients describing access strategies for revision or exploration of the Charité lumbar total disc replacement system (DePuy Spine, Raynham, Massachusetts), reported 1 case of RPL with hydronephrosis after 2-level total disc replacement at L4-5 and L5-S1 treated with laparoscopic marsupialization after failure of nonoperative strategies.…”
Section: Discussionmentioning
confidence: 99%